THE IMPORTANCE OF THE FAMILY ENVIRONMENT, INTEREST IN ENTREPRENEURS AND CHARACTER IN DOING ENTREPRENEURS FOR STUDENT ACTIVITIES IN ENTREPRENEURSHIP - Primadona (Jurnal Kelola: Jurnal Ilmu Sosial, 2021)
The number of unemployed causes the younger generation to be more productive to get out of unemployment. One of the steps to be productive is to carry out entrepreneurial activities. But of course, to do good entrepreneurship, it is necessary to identify various aspects that can affect entrepreneurial activities themselves. This study will attempt to examine the influence of entrepreneurial character, entrepreneurial interest, and family environment on entrepreneurial activities for students in the West Sumatra Province. This research will be assisted by the SPSS version 21 application. This study found that the entrepreneurial character and family environment significantly influenced students’ interest in entrepreneurship. Then the entrepreneurial character and family environment also have a significant influence on activities in entrepreneurship. Finally, interest in entrepreneurship has a negative and significant impact on entrepreneurial activities for students in the West Sumatra Province.